Transformasi Kompetensi Ustadz melalui Program Kader Dai di Madrasah Diniyah Takmiliyah At-Tahdzib - Bustanul Arifin Arifin; Moh. Ulumuddin; Ahmad Insya Ansori; Hanik Latifah (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
The 2024 Kader Dai Program at Madrasah Diniyah Takmiliyah At-Tahdzib is designed to transform the roles and competencies of Islamic teachers (ustadz) by strengthening the implementation of Islamic legal values within society. Utilizing an experiential learning approach and continuous capacity-building, the program enables ustadz to deepen their religious knowledge while simultaneously cultivating leadership, communication skills, and adaptability to contemporary issues. This transformation is evident in the evolving roles of ustadz—from merely transmitting knowledge to serving as mentors, facilitators of religious dialogue, and social mediators who actively employ information technology to expand the reach of Islamic outreach (da’wah). The results demonstrate that holistic and sustained guidance can produce ustadz who are relevant, adaptive, and effective in contextualizing Islamic law amidst the complexities of modern society.